Outcomes-based contracts and the hidden turn to public value management - Kimmitt, Jonathan; Muñoz, Pablo (Organization (London, England), 2024)
Despite long-standing criticisms of the paradigm, New Public Management (NPM) retains a strong influence over organizations in public administration. Social Impact Bonds (SIB) are an outcomes-oriented investment entity which has emerged from NPM with grand promises of social change. Building on a longitudinal case study of a health-based SIB, this paper identifies how key actors move away from NPM by resisting such management principles and shift toward Public Value Management (PVM). The paper finds that this is possible when the public interest and performance objectives are designed with a public value orientation whilst other NPM principles shift over time through resistance and negotiation. The paper provides insight into how key actors re-organize to embed public value in a financing and public service delivery structure that is often regarded as flawed and inefficient. The paper offers several contributions to public value literature, including the role of the state, as well as the emerging literature on SIBs and outcomes-based contracts.